Analysis of single nucleotide polymorphisms in miRNA genes and their role in schizophrenia etiology - Bolaños Palmieri, Patricia (2014)
Schizophrenia is a severe neuropsychiatric disease that in spite of having a clear genetic component in its etiology, the genes involved have not yet been unequivocally identified and only explain a small percentage of the cases. Within the complex scenario of gene expression regulation, microRNAs have been implicated in the post-transcriptional regulation of mRNA. This mechanism of protein synthesis regulation has been linked to the correct formation of synapses, which translates in the ability to learn and other higher cognitive functions. Methods: miRNA candidate genes were established according to their genomic location and previous reports of differential expression in schizophrenic brains. Further in silico analysis was carried out in order to establish the targets for miRNA regulation and their relationship to the pathology. SNP genotyping analyses were performed in a sample of schizophrenic probands and their nuclear family members from Costa Rica, in order to establish an association to disease status. Results: A search of the available literature revealed a total of 60 miRNA differentially expressed in brains of schizophrenic patients, of which 12 were located in genomic regions of interest. Amongst the targets of posttranscriptional regulation are the Neurotrophin signaling pathways that have been implicated in important synaptic and neuronal processes. This result strengthens the hypothesis that these miRNA can be involved in disease etiology. Of the 4 SNPs genotyped only rs41283391 on miR-195 was polymorphic in our sample, however the association to Schizophrenia diagnosis was not significant (n = 317, Z = 0.797, p = 0.42). Conclusion: This research project adds further information to the hypothesis of the involvement of the miRNA regulation pathway in neuropsychiatric diseases. Even though the analysis of these particular SNPs gave no evidence of association, it is plausible that further sequence analysis could reveal more information about variants that could influence disease etiology. Another important outcome of this project is the establishment of further hypothesis for future research projects, some of which are already underway.